Analysis of btuB receptor function by use of nonsense suppression. - Hunter, M G (1982)
Informational suppression of btuB nonsense mutants allows the study of the effect of known, single amino acid substitutions on receptor function. We found that ligand uptake is largely unaffected by such amino acid changes. The few instances in which certain substitutions destroyed sensitivity to the two lethal agents (phage BF23, colicin E3) without affecting vitamin B12 uptake suggest a common region on the btuB receptor involved in the binding of these proteinaceous agents.